2006
DOI: 10.1249/01.mss.0000227536.13175.52
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Body Position on Slide Boarding Performance by Cross-Country Skiers

Abstract: The current results indicate that for a short duration, the deeper sit provides sufficient advantages that it may prove useful to apply such a position in sprint ski-skating, even though the use of the upper extremities in poling will be strongly hampered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 13 publications
5
18
0
Order By: Relevance
“…In Leirdal et al [3], the moderate position of the skier is similar to gear 5 in this study. The results in Leirdal for FD were ~17 N and ~25 N for the static and dynamic test (air velocity 10m/s), respectively, which gives a CDA of 0.28 m 2 and 0.42 m 2 .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In Leirdal et al [3], the moderate position of the skier is similar to gear 5 in this study. The results in Leirdal for FD were ~17 N and ~25 N for the static and dynamic test (air velocity 10m/s), respectively, which gives a CDA of 0.28 m 2 and 0.42 m 2 .…”
Section: Discussionsupporting
confidence: 80%
“…By using an object with a predetermined area ( ), it is possible to correlate this area with the number of image pixels ( ) to get the area units ( ) corresponding to each pixel (3). In this case, a rectangular white board with a height and width of 1.80 and 0.25 m was used as a reference area (0.45 m 2 ), see …”
Section: Skier Projected Frontal Area Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, a relatively complex technique, such as in cross-country skiing, compared with more simple techniques, such as cycling, may be a prerequisite for eYciency to be strongly aVected by the execution of the technique. Notably, the GE in this study is close to what is found in speed skating (de Koning et al 2005) and slide boarding (Leirdal et al 2006) with around 15%, but lower than in cycling with »20% (Ettema and Loras 2009).…”
Section: Metabolic Rate and Gross Eyciencysupporting
confidence: 83%
“…For drag and front area we assumed C d A = 0.55 m 2 when speed v 6 10 m/s and C d A = 0.35 m 2 in deep tuck position when v > 10 m/s. See references Leirdal, Saetran, Roeleveld, et al (2006) and Spring, Savolainen, Erkkila, Hamalainen, and Pihkala (1988) to simulate Eq. (5) depends on a, b, c. The experimental speed v e (i) was calculated as incremental distance divided by incremental time between two subsequent time measurements.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%